ENHANCEMENT OF MOTHERS AND CADRE ROLES IN FIRST 1.000 DAYS OF LIFE AS STUNTING PREVENTION AND DETECTION AT THE MOROKREMBANGAN PRIMARY HEALTH CENTER SURABAYA - Lucky Prasetiowati; Sulistiawati; Widati Fatmaningrum; Eighty Mardiyan Kurniawati; Hanna Dyahferi Anomsari; Rimbun (Jurnal Layanan Masyarakat, 2023)
Stunting is a condition in which children under five years old fail to thrive due to chronic malnutrition in the first 1000 days of life and the height is below the height chart (<-2 SD) on standard age. Although stunting has negative great impact on the child growth and development, parents frequently are not concert about it due to lack of information regarding stunting.  The COVID-19 pandemic also contributes on fulfillment of nutritious food, non-routine checks for the child growth and development at the posyandu, and even stopped posyandu activities. Therefore, it is still challenging to detect the incidence of stunting in the community. This program aims to increase the knowledge and raise awareness of the importance of the first 1000 days if life in a child's growth and development also to increase the cadre skill in the early detection of stunting. The community service activity was held in the area of the Morokrembangan Primary Health Center include health promotion and training for early detection of stunting through anthropometric examination for posyandu cadre, pregnancy mother and mother of under 5 years old child. Evaluation was done by measuring the increasing of participants knowledge about stunting through pretest and posttest. There was a significant difference (p = 0.000) between the pretest and posttest. It means that this program activities have succeeded in increasing the knowledge of mothers and cadre.  A better understanding of the first 1000 days of life can improve people's behavior to prevent stunting in community.